FUNGSI DAN PERAN SINTAKSIS PADA KALIMAT TRANSITIF BAHASA JEPANG DALAM NOVEL CHIJIN NO AI KARYA TANIZAKI JUNICHIRO - Dwi Antari, Ni Kadek Nomi (Humanis; Volume 6. No. 3. Maret 2014, 2014)
This research aims at function and role of syntax in Japanese transitive sentences in the Japanese novel Chijin no Ai taken from Tanizaki Junichiro. The theoris used in this research are Tagmemik taken from Kenneth L. Pike and case grammar theory taken from Carles. J. Fillmore. Observation method was used as a data collecting method, while distributional method for data analysis. The result of data analysis was then presented with formal method and informal method. Based on the data that has been analyzed, the results of this research indicate that the syntactic function consists of subject, predicate, object, and modifier which may be filled by a word or phrase. Predicate function is filled by verbs can be divided into two, namely active transitive verbs and passive transitive verbs. Modifier functions can be divided into time, tools, places, and circumstances. Syntactic role is divided into eight cases contained in the word or phrase, which is the case stating agentive, instrumental, objective, expressed dative, purpose (goal), locative, comitative, and benefactive.
Keywords: words and phrases, syntactic function, syntactic role 1. Latar